2021
DOI: 10.3389/fmed.2021.616489
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gut Microbiota in Chronic Itch-Evoked Novel Object Recognition-Related Cognitive Dysfunction in Mice

Abstract: The high incidence of patients with chronic itch highlights the importance of fundamental research. Recent advances in the interface of gut microbiota have shed new light into exploring this phenomenon. However, it is unknown whether gut microbiota plays a role in chronic itch in rodents with or without cognitive dysfunction. In this study, the role of gut microbiota in diphenylcyclopropenone (DCP)-evoked chronic itch was investigated in mice and hierarchical cluster analysis of novel object recognition test (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…However, a decrease in the serotonin level also causes cognitive deterioration. Previous studies indicated that serotonergic neuron has a primary role in cognition (Sun et al, 2021;Shine et al, 2022). The alternation of the 5-HT neuron system significantly affects NCDs.…”
Section: Discussionmentioning
confidence: 99%
“…However, a decrease in the serotonin level also causes cognitive deterioration. Previous studies indicated that serotonergic neuron has a primary role in cognition (Sun et al, 2021;Shine et al, 2022). The alternation of the 5-HT neuron system significantly affects NCDs.…”
Section: Discussionmentioning
confidence: 99%
“…The significance testing was two-tailed, and p < 0.05 was statistically significant. The rats that underwent the SMIR surgery were divided into the susceptible group (cognitively compromised pain rats) and the unsusceptible group (cognitively normal pain rats) based on the Ward method and Euclidean distance square as distance measurement using the hierarchical cluster analysis of the data from the novel object recognition test and the Y-maze test [ 31 ]. Statistical analyses and graphs (except the 16S rRNA microbiome sequencing analyses) were performed with the Adobe Illustrator Artwork 14.0 and GraphPad Prism 8.0.…”
Section: Methodsmentioning
confidence: 99%
“…To generate the pseudo-germ-free animal model, we provided the experimental rats with vancomycin hydrochloride (500 mg/L), ampicillin sulfate (1 g/L), neomycin sulfate (1 g/L), and metronidazole (1 g/L) in their sterile drinking water for 2 weeks [9,31]. Each mixed fecal sample (1 g) from different unsusceptible or susceptible rats was suspended in 10 mL of sterile phosphate-buffered saline and vigorously vortexed for 5 min.…”
Section: Microbiota Depletion and Fmtmentioning
confidence: 99%
See 1 more Smart Citation
“…Fecal samples were collected immediately after defecating in a sterilized centrifuge tube. The filter paper was changed after each mouse as our previously study ( Li et al, 2021 ). Fecal samples were stored in a − 80°C freezer.…”
Section: Methodsmentioning
confidence: 99%